Wielkość ekonomiczna jako czynnik różnicujący wyniki produkcyjne i ekonomiczne gospodarstw rolnych w regionie Pomorza i Mazur - Bórawski, Piotr (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
Production and economic results according to economic sixe ESU in Pomorze and Mazury region were presented in the paper. The number of farms has incresed in all farms groups in the analyzed period. The value of production has decresed in following farms: very small, average-small, average-large and large in 2004–2006 years. But, the production has incresed in very large farms in 2004–2006 years. The economic results has increased in almost all types of farms. The decrese of economic results was observed in large farms. During to survey it was observed the increse of production calculated per farm anf 1 ha farmland. It was the result of production efficiency improvement and increse of animals. The income calculated per 1 employed person has incresed as the results of work hire in the farms